1999
DOI: 10.1007/s002280050695
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic and interindividual variabilities of platelet sulfotransferases activity in Italians and Finns

Abstract: This study shows that platelet catechol sulfotransferase activity is greater in Italians than Finns and that the activity of phenol sulfotransferase is gender regulated in Finns but not in Italians. Thus, interethnic differences exist in platelet sulfotransferases between Italians and Finns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that SULTs have substrate-dependent effects and they exhibit marked differences in tissue distribution as well as their sensitivity to thermal inactivation and inhibitor [51]. Moreover, previous studies have shown gender-specific differences for SULT activity [5255]. Nowell et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that SULTs have substrate-dependent effects and they exhibit marked differences in tissue distribution as well as their sensitivity to thermal inactivation and inhibitor [51]. Moreover, previous studies have shown gender-specific differences for SULT activity [5255]. Nowell et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, thiopurine methyltransferase (TPMT) activities were lower in hepatic tissues of women compared with men (Szumlanski et al 1992), and levels of catechol-O-methyltransferase activity were also lower in women relative to men (Boudikova et al 1990). Finally, phenol sulfotransferase activity was more than 60 % lower in Finnish women than men (Brittelli et al 1999). …”
Section: Metabolismmentioning
confidence: 94%
“…Ethnic variation in platelet enzymatic activity has also been reported. A study by Brittelli et al (1999) showed that SULT1A1 activity was significantly different between Spaniards and Finns, and in the case of the Finnish population, phenotype also varied by gender. Platelet SULT1A1 phenotype also tends to be higher in African Americans compared to Caucasians (Anderson et al, 1988;Nowell et al, 2000).…”
Section: Sult1a1mentioning
confidence: 99%